2010
DOI: 10.1093/ndt/gfp724
|View full text |Cite
|
Sign up to set email alerts
|

Sulodexide ameliorates early but not late kidney disease in models of radiation nephropathy and diabetic nephropathy

Abstract: Our data show that sulodexide can reduce the early, but not late, proteinuria in radiation nephropathy in rats. In addition, sulodexide did not affect urine TGF-beta established albuminuria or mesangial matrix expansion in a chronic model of diabetic kidney disease in mice. Although sulodexide may affect TGF-beta activation in radiation nephropathy, this effect appeared insufficient in this model to inhibit the expressions of PAI-1 and collagen and reduce accumulation of extracellular matrix. These results may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 32 publications
1
19
1
Order By: Relevance
“…In addition to the likely involvement of TGFβ and PAI1, Ang II is certainly the principal mediator of this process. The results of this study showed that sulodexide (15 mg/kg/day by subcutaneous injection, 6 days/week for 4, 8 and 12 weeks) is effective in reducing the early, but not late, indicators of radiation nephropathy and has no influence on renal damage, despite sulodexide considerably diminishing TGFβ activation (61).…”
Section: Physical Models -Radiation Nephropathymentioning
confidence: 73%
“…In addition to the likely involvement of TGFβ and PAI1, Ang II is certainly the principal mediator of this process. The results of this study showed that sulodexide (15 mg/kg/day by subcutaneous injection, 6 days/week for 4, 8 and 12 weeks) is effective in reducing the early, but not late, indicators of radiation nephropathy and has no influence on renal damage, despite sulodexide considerably diminishing TGFβ activation (61).…”
Section: Physical Models -Radiation Nephropathymentioning
confidence: 73%
“…In rats with radiation nephropathy, sulodexide did not change renal function, but lowered proteinuria; and in diabetic mice, sulodexide had no effect on proteinuria. 118 In rats with adriamycin nephropathy, sulodexide markedly decreased albuminuria and reverted from diffuse to segmental foot process involvement. It also reduced levels of a molecule known to degrade the proteoglycan layer of endothelium (heparanase messenger RNA), a cytoskeleton stabilizer (desmin), and a slit diaphragm component (CD2AP).…”
Section: Novel Agents In Diabetic Nephropathymentioning
confidence: 99%
“…Recent experimental models suggest that sulodexide may ameliorate early but not late kidney disease. 33 As discussed previously, 32 potential confounding factors must be mentioned. First, although previous pharmacokinetic studies demonstrated oral absorption of sulodexide from the gastrointestinal tract, this was at levels that did not alter hemostasis.…”
Section: Discussionmentioning
confidence: 99%